Early identification and optimal management of carbapenem-resistant Gram-negative infection. (February 2021) - Bedos, J.P.; Daikos, G.; Dodgson, A.R.; Pan, A.; Petrosillo, N.; Seifert, H.; Vila, J.; Ferrer, R.; Wilson, P.
Summary: Background: Carbapenem resistance in Gram-negative bacteria is associated with severe infections in the hospital setting. No uniform screening policy or agreed set of criteria exists within the EU to inform treatment decisions for infections caused by carbapenem-resistant Gram-negative bacteria. Aim: To develop a range of consensus statements to survey experts in carbapenem resistance, to identify potential similarities and differences across the EU and across specialties. Methods: The survey contained 43 statements, covering six key topics relating to carbapenem-resistant organisms: microbiological screening; diagnosis; infection control implementation; antibiotic stewardship; use of resources; and influencing policy. Findings: In total, 136 survey responses were received (66% infectious disease specialists, 18% microbiologists, 11% intensive care specialists, 4% other/unknown) from France, Germany, Greece, Italy, Spain, and the UK. High, or very high, levels of agreement were seen for all 43 consensus statements, indicating good alignment concerning early identification and optimal management of infection due to carbapenem-resistant organisms. Conclusion: We offer the following recommendations: (1) screening is required when a patient may have been exposed to the healthcare system in countries/hospitals where carbapenem-resistant organisms are endemic; (2) rapid diagnostic tools should be available in every institution; (3) all institutions should have a specific policy for the control of carbapenem-resistant organisms, which is routinely audited; (4) clear strategies are required to define both appropriate and inappropriate use of carbapenems; (5) priority funding should be allocated to the management of infections due to carbapenem-resistant organisms; and (6) international co-operation is required to reduce country-to-country transmission of carbapenem-resistant organisms.